Sicca symptoms in Thai patients with rheumatoid arthritis, systemic lupus erythematosus and scleroderma: A comparison with age-matched controls and correlation with disease variables - Suparaporn Wangkaew (2018)
This study was performed to determine the prevalence of ocular and oral sicca symptoms in Thai patients with rheumatoid arthritis (RA), systemic lupus erythematosus (SLE), and scleroderma (Scl). The ocular symptoms and sign (the Schirmer's 1 test) and the oral sicca symptoms and sign (the Saxon's test) in each of 50 RA, SLE and Scl patients were compared with their age-matched controls. The correlation between the presence of sicca symptoms and signs with their clinical activity was also determined. Ocular sicca symptoms were found more common in patients with RA (38% vs 18%, p < 0.05), SLE (36% vs 14%, p < 0.05) and Scl (54% vs 16%, p < 0.01), and oral sicca symptoms were found more common in SLE (22% vs 0%, p < 0.01), and Scl (16% vs 4%, p < 0.05) than their controls. However, only RA patients had a significantly higher proportion of positive Schimer-1 test compared with their controls (p < 0.01). There was no strong correlation between sicca symptoms or signs and other clinical or laboratory variables (age, disease duration, disease activity, disease severity, and antibody to Ro and La antigens) in these three groups. In conclusion, sicca symptoms were seen significantly more common in Thai patients with connective tissue diseases, but the symptoms did not show a good correlation with the clinical and laboratory variables.